Enhancing Junior High School Students' Self-Efficacy through Self-Reflection-Based Classical Guidance - Ayu Nursalama; Suharni; Nindia Harnes Prima Aidha (Darul Yasin Al Sys, 2026)
Low self-efficacy among junior high school students can undermine self-confidence and active engagement in learning; however, research positioning self-reflection as the core intervention in Guidance and Counseling services remains limited. This study aims to examine the effectiveness of self-reflection-based classical guidance services in improving the self-efficacy of ninth-grade students at a public junior high school in Madiun. A quantitative approach with a one-group pretest–posttest design was employed, involving 30 students selected through total sampling. Data were collected using a self-report scale and analyzed using a paired-samples t test and Cohen’s d_z. The findings reveal a statistically significant increase in the mean self-efficacy score from 142.70 at pretest to 171.60 at posttest, t(29) = −12.15, p < .001, with a very large effect size (d_z = 2.22). However, the decrease in the minimum score from 78.00 to 74.00 suggests that some students may have undergone a metacognitive calibration process toward a more realistic self-assessment. The study concludes that self-reflection-based classical guidance services are effective in enhancing students’ self-efficacy. These findings contribute to the development of student-centered Guidance and Counseling practices by emphasizing structured reflection as a central component of classical guidance and highlight the need for follow-up individual counseling for students requiring more targeted support.